PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Pada Dosen STIE Indonesia Banjarmasin) - Aulia Sindy Perwisari; Dahniar; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
The aim of the research is to identify and analyze the effects of transformational leadership and job satisfaction simultaneosly and partially on Organizational Citizenship Behavior (OCB) of the lecturers of STIE Indonesia Banjarmasin. This type of the research is a quantitative explanatory research with a population of 35 people, the sampling technique used was purposive sampling, and data collection technique applied by using questionnaires. Respondents who returned the questionnaire were 30 lecturers of STIE Indonesia Banjarmasin. The instrument used to test the hypothesis is multiple linear regression by utilizing SPSS software ver.18.0. The result of this study showed that (1) the variables of transformational leadership and job satisfaction simultaneously influence the OCB of the lecturers of STIE Indonesia Banjarmasin, (2) the transformational leadership has no effect on the OCB, and (3) job satisfaction has effects on the OCB of the lecturers of STIE Indonesia Banjarmasin.